The Acute Effect of Static Stretch Alone and in Combination with Dynamic Exercise on Some Functional Indices in Athletes with and without Hamstring Tightness - Maryam Azamifar; Rahman Sheikhhoseini; Rasoul Eslami (Shiraz University of Medical Sciences, 2020)
Background: The aim of this study was to investigate the acute effects of static stretch alone and in combination with plyometric exercises on some functional indices in athletes with and without hamstring tightness. Methods: For this controlled laboratory study, 20 female athletes with hamstring tightness and 15 female athletes with normal hamstring participated voluntarily in static stretching exercises or stretching in combination with plyometric exercises in two consecutive days after warm up, with a random stretching order. The maximum voluntary hamstring isometric strength, maximal vertical jump, and Y balance test were also measured. Results: The results indicated that both static stretching and stretching in combination with plyometric exercises may affect balance more adversely in athletes with hamstring tightness. Both types of stretching programs may also cause adverse effects on balance, muscle strength, and maximal vertical jump (P <0.05). Conclusion: According to the results, the level of balance of individuals with hamstring tightness may be affected more adversely through static stretching exercises. Thus, we suggest that the static stretch should not be prescribed for athletes with hamstring tightness at the warm up of training sessions.